Satu Ranjang Multi Keyakinan: Studi tentang Persaudaraan Umat Beragama di Kecamatan Papar Kabupaten Kediri: One Bed, Multiple Faiths: A Study on Interreligious Brotherhood in Papar District, Kediri Regency - Syamsun Ni’am (Fenomena, 2012)
The word "companionship" feels very strange when globalization, with its various effects, has gradually eroded the human aspects of every individual. Some people no longer respect one another. Indonesia—as a highly plural and multicultural nation—on one hand, can become a great power when every social aspect is respected and given the opportunity to develop, thereby enriching the social atmosphere and national culture. On the other hand, plurality and multiculturalism can become a destructive force when the state favors one group based on ethnicity, culture, or religion over others, depriving each aspect of equal opportunities to grow. Therefore, we must learn from the traditions once practiced by our ancestors, so that conflicts—especially those with SARA (Ethnicity, Religion, Race, and Intergroup) undertones—can be truly eliminated. Furthermore, these traditions can serve as a potential foundation for the nation's future development. Kata "persaudaraan" terasa sangat asing ketika globalisasi dengan berbagai dampaknya telah secara bertahap menghancurkan aspek kemanusiaan setiap individu. Beberapa orang tidak lagi saling menghargai. Indonesia—sebagai bangsa yang sangat plural dan multikultural—di satu sisi akan menjadi kekuatan besar ketika setiap aspek sosial dihargai dan diberi kesempatan untuk berkembang, sehingga setiap aspek dapat memperkaya suasana sosial dan budaya bangsa. Di sisi lain, pluralitas dan multikultural akan menjadi kekuatan destruktif ketika negara mendukung satu kelompok berdasarkan etnis, budaya, atau agama di atas kelompok lain, sehingga setiap aspek tidak memiliki kesempatan yang sama untuk berkembang. Oleh karena itu, kita perlu belajar dari tradisi yang pernah hidup dan dikembangkan oleh nenek moyang kita, agar konflik—terutama yang bernuansa SARA (Suku, Agama, Ras, dan Antar golongan)—dapat benar-benar dihilangkan. Lebih jauh, tradisi tersebut dapat menjadi potensi untuk pembangunan bangsa di masa depan.